Non-Muslims` citizenship in Islamic law: a critique from the constitutional perspective = Kewarganegaraan non-Muslim dalam undang-undang Islam: satu kritikan dari perspektif perlembagaan - Haneef, Sayed Sikandar Shah (International Islamic University Malaysia, 2012)
Non-Muslim permanent residents of an Islamic state were traditionally conferred a kind of nationality status which was juridically defined as dhimmah (protected). With the demise of Islamic Caliphate System and the constitutional collapse of its underlying principles and the subsequent emergence of nation-states, its retention, redefinition, or even abandonment became a subject of intense debate particularly among modern jurists. By and large, within juristic community the discourse has followed two divergent trends, namely the paradigm of traditionalists and that of re-constructionists. The former regards dhimmah as a permanently fixed concept and an integral part of immutable laws of the sharÊ‘ah, while the latter views it as a historically contingent institution capable of adaptation to fit the notion of modern citizenship in postcaliphate modern nation states. Consequently, this tussle has given rise to two divergent discourses among the researchers outside the Islamic faith. Some hail the traditionalist approach as more authentic voice, while others applaud the reconstructionist project as more sensible alternative paradigm capable of harmonizing Islamic law with modern notion of citizenship for Non-Muslim subjects of a Muslim state as envisioned by Universal Declaration of Human Rights (see article 15). This article proves that in both sides of the divide the emphasis on constitutional dimension of the issue has not been sufficiently explored hence attempts to place the debate in its true context so as to avoid the folly of singularly insisting on reinstating the dhimmah without the ability to revive its constitutional bases or wholly equating it with the concept of citizenship in a liberal sense as some make us to enunciate.